Significado regional dos depósitos neogénicos continentais da área de Vila de Rei (Portugal Central) - Barra, António (2016)
In the Vi la de Rei arca (Central Portugal) the continental deposits ofthe Lower Tagus Tertiary 8asin lay upon the pediment of me Portuguese Central Chain. Three ronglomerate units are recorded from me base upwards. separated by regional or basinal unconfonnities: Conglomerados de Rio de Moinhos (RM); Conglomerados de Serra de Almeirim (SA) and Conglomerados de Vila de Rei (VR). The first two units (KM and SAl have been si les of gold exploitation in huge optn pit mines probably dunng Roman colonisation times. The contact ofthis units, on thc Paleozoie basement or on the Paleogene unil Grés de Monsanto, is unconfonn, defining in both limits a large nondepositional andlor erosional hiatus. Those conglomerates seal the scdimcntation ofthe Lower Tagus Tertiary Basin along irs northem border. Taking lnto account lhe significance /lssigned to their basinal unconfonnity limits, lhe uplift ofthe Portuguese Centra! Chain. and thc facl ofthis continental units yielded no fossils with chranostratigraphic significanee, they have been eonsidered ranging fram Uppcr Miocene to lhe beginning ofthe Qualemary. Finally, a lithostratigraphic equivalence with lhe Neogenic units ofthc Bierzo and Duema basins (NW ofthe Iberian Peninsula), where exploitalions from Roman limes are also evident, is presented.